The Development of Interactive Online Lessons on System Thinking and Problem Analysis for Burapha University Undergraduate Students - Panich, Weerapun (HRD Journal, 2022)
The purposes of this study were to 1) develop interactive online lessons on system thinking and problem analysis for undergraduate students at Burapha University; 2) Evaluate the efficiency of Interactive online lessons on system thinking and problem analysis according to the criteria E1/E2 (80/80); 3) Assess students’ system thinking and problem analysis skills after studying with interactive online lessons on system thinking and problem analysis; 4)Compare scores between pre-test and post-test. This study is a research and development based on the ADDIE Model processes which are 1) Analysis 2) Design 3) Development 4) Implementation 5) Evaluation. Online lesson quality was assessed by 5 educational technology and System thinking specialists. The sample consisted of 40 undergraduate student of Burapha University who studied the subject of System Thinking and Problem Analysis in the first semester of the academic year 2020 which is selected by a cluster random method. The research instruments included: 1) The interactive online lessons on system thinking and problem analysis 2) Online lessons quality assessment form 3) Pre-test and Post-test 4) Assess student’s systems thinking and problem analysis skills. The data was analyzed by using percentage, means, Standard Deviation, efficiency E1/E2 and t-test. The results of this study found that: 1. The interactive online lessons on system thinking and problem analysis for undergraduate students at Burapha university is developed which contains 4 units as follows: 1) Fundamentals of system thinking 2) analytical thinking and tools for thinking development 3) learning organizations and systems thinking processes, and 4) problem analysis by system thinking. The overall assessment by experts was at a high level ( = 4.15, S.D. = 0.23). 2. The efficiency of Interactive online lessons on system thinking and problem analysis for undergraduate students at Burapha University, E1/E2, for unit 1 is 80.16 /81.00, unit 2 is 82.71 /81.75, unit 3 is 89.79 /80.25 and unit 4 is 87.36 /82.50 which more than the criterion set 80/80. 3. Students’ system thinking and problem analysis skills after study on interactive online lessons on system thinking and problem analysis are at the highest level (80.21 %) 4. The post-test score after study on interactive online lessons on system thinking and problem analysis is higher than pre-test at .05 level significant.